Does Your Organization Assess Risk Culture? If Not, It Should. Here's How - Miller, Paul (Frontiers in Research Metrics and Analytics, 2022)
Risk culture is an important subset of organizational culture that Enterprise Risk Management (ERM) program managers should assess. Insights into the organization’s risk culture can be found in behavioral metrics. Valuable behavioral metrics are present in workforce climate assessments such the Federal Employee Viewpoint Survey (FEVS) . Training evaluation frameworks, such as the Kirkpatrick Model , set the foundation for collecting and analyzing behavioral metrics. These sources of behavioral metrics should be utilized in making ERM program decisions, especially regarding risk management policies, training, and communications. A good risk culture assessment offers clues into the risk mentality of decision makers in the organization. ERM program managers would serve their organizations well by knowing the risk mentality of people before important decisions are made.